Determining Taftāzānī’s madhhab: Insights after the Decline Paradigm - Navid Chizari (Darulfunun Ilahiyat)
Modern scholarship has largely rejected the decline paradigm, allowing for the evaluation of the Islamic intellectual tradition on its own terms. Rather than viewing the commentary tradition as a sign of decline, scholars have sought to understand the different literary genres and their functions. However, a gap has emerged between the insights gained from works published in Anglo-Saxon languages and those published in Arabic and Turkish. This paper presents insights from recent works published in the Muslim World on the commentary tradition, focusing on the concept of taqrīr and how it helps to solve an issue regarding the debate surrounding Saʿd al-Dīn al-Taftāzānī’s madhhab in fiqh and kalām. The conclusion of the investigation argues that al-Taftāzānī should be considered an Ashʿarī in kalām and Shāfiʿī in fiqh based on a careful reading of his works in the context of the commentary tradition.